Effect of variety and processing method on functional properties of traditional sweet potato flour ("elubo") and sensory acceptability of cooked paste ("amala"). Issue 6 (7th August 2014) - Fetuga, Ganiyat; Tomlins, Keith; Henshaw, Folake; Idowu, Michael
<x xml:space="preserve">Abstract</x> The quality of flour ("elubo") and cooked paste ("amala") from three varieties of sweet potato roots and two processing methods were investigated. Acceptable sweet potato "amala" were obtained from yellow‐fleshed varieties irrespective of the processing method. Flour that produced acceptable "amala" were characterized by lower values of protein (2.20–3.94%), fiber (1.30–1.65%), total sugar (12.41–38.83 μg/mg), water absorption capacity (168–215 g/100 g), water solubility (8.29–14.65%), swelling power (0.52–0.82 g/g), and higher peak time (6.9–8.7 min). <boxed-text content-type="graphic" id="fsn3161-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>